Human Beta-Defensin-3 and Di-Aminoimidazole as Antimicrobial Adjuvants Against Multidrug-Resistant Acinetobacter baumannii - Taher Habash, Ruqayah; Dhuha Mahdi Jabir (Journal of Biomedicine and Biochemistry, 2026)
Background: Multidrug-resistant (MDR) Acinetobacter baumannii is a major cause of hospital-acquired infections with high morbidity and mortality. Resistance has quickly grown, making it harder to find effective treatments. This has led to the need for new approaches, like antimicrobial adjuvants that make existing antibiotics work better.Objective: This study assessed the efficacy of human beta-defensin-3 (hBD-3) and di-aminoimidazole (2-AI) as antimicrobial adjuvants in conjunction with conventional antibiotics against multidrug-resistant A. baumannii.Methods: We evaluated three MDR clinical isolates and one reference strain (ATCC19606). Used broth microdilution to find the minimum inhibitory concentrations (MICs) of hBD-3, 2-AI, and four antibiotics: ampicillin-sulbactam, imipenem, ceftazidime, and ciprofloxacin. A sub-MIC quantity of 50 µg/mL of hBD-3 and 2-AI was employed in combinatorial experiments. Experiments three times and used the paired t-test and Wilcoxon signed-rank test to look at the results.Results: A notable decrease in MIC occurred when ampicillin-sulbactam was administered in conjunction with either hBD-3 or 2-AI across all isolates. There was also a big improvement with imipenem+ hBD-3, however imipenem + 2-AI had no impact. No substantial synergy was seen for combinations of ceftazidime or ciprofloxacin with either adjuvant.Conclusion:hBD-3 and 2-AI showed potential, as antimicrobial adjuvants, especially; when combined with β-lactam antibiotics. However, due to the limited number of isolates examined, these findings must be considered preliminary, and further studies with larger sample sizes are required.